High-content lithium carbonate tailings paving stone and preparation method thereof
Patent Information
- Application Number
- CN202511519110.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-23
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-10-23
AI Technical Summary
It is difficult to balance the permeability and mechanical strength of existing paving stones. When the permeability is high, it is easy to reduce the density and mechanical strength of the paving stones. The mechanical strength of the existing breathable bricks is not good.
Using high-dosage lithium carbonate tailings and polyether additives, paving stones are prepared by crushing, mixing, and sintering. The lithium oxides in the lithium carbonate tailings form a low-melting glass phase with the raw materials, and the polyether additives improve the fluidity and dispersibility of the mixture. After high-temperature sintering, pores are formed, which enhances the mechanical properties.
It improves the permeability and mechanical strength of paving stones, increases apparent porosity and water absorption, extends service life, and is suitable for outdoor scenarios to quickly infiltrate rainwater, reducing the burden on urban drainage systems.
Abstract
Description
Technical Field
[0001] This invention relates to the field of paving stone technology, specifically to a paving stone with high lithium carbonate tailings content and its preparation method. Background Technology
[0002] Paving stones are a type of building material used for paving surfaces, widely used in plazas, sidewalks, and urban landscapes. They mainly include natural stone paving stones, artificial stone paving stones, and ceramic paving stones. Permeable paving stones have excellent water absorption and permeability, allowing rainwater to quickly infiltrate the ground, preventing surface flooding, reducing the burden on urban drainage systems, and helping to replenish groundwater.
[0003] The permeability of paving stones is positively correlated with their porosity; however, a higher porosity can easily reduce the density and mechanical strength of the paving stones. Patent CN115784710B discloses breathable paving bricks and their production method. Using feldspar sand, bentonite, washed sand, mixed soil, kaolin, water-reducing agent, and reinforcing agent as raw materials, the prepared breathable bricks have good permeability and can absorb harmful gases. However, these paving bricks lack good mechanical strength, which is detrimental to extending their service life. Summary of the Invention
[0004] (a) Technical problem to be solved: In view of the shortcomings of the existing technology, the present invention provides a paving stone with high lithium carbonate content tailings and its preparation method, which improves the mechanical properties and permeability of the paving stone.
[0005] (II) Technical solution: A paving stone for high-content lithium carbonate tailings, comprising 25-33 parts by weight of terrazzo, 42-57 parts by weight of aggregate, 5.3-7.4 parts by weight of bentonite, 2.2-3.5 parts by weight of magnesia refractory mortar, 4.7-7.6 parts by weight of bauxite, 6-11 parts by weight of clay, 12-18 parts by weight of kaolin, and 0.3-0.8 parts by weight of polyether additives.
[0006] Preferably, the aggregate includes coarse aggregate and fine aggregate in a mass ratio of (90-96):(4-10).
[0007] Preferably, the coarse aggregate consists of coarse sand with a particle size of 2-5 mm and lithium carbonate tailings with a particle size of 5-15 mm.
[0008] Preferably, the fine aggregate is fine sand with a particle size of 0.6-1.2 mm.
[0009] Preferably, the mass ratio of coarse sand to lithium carbonate tailings is (65-85):(15-35).
[0010] Preferably, the preparation method of the polyether additive is as follows: (1) Add polyetheramine and glutaraldehyde to ethanol, stir to carry out the reaction, add sodium borohydride, continue the reaction, reduce the Schiff base C=N bond, distill under reduced pressure, add the product to dichloromethane, wash with saturated sodium chloride, distill under reduced pressure on the organic phase, dry, and obtain the polyether precursor.
[0011] (2) Add 100:(6-15) of polyether precursor and maleic acid to the ethanol aqueous solution, stir to react, add sodium hydroxide to neutralize, dry to remove ethanol and water, wash with saturated sodium chloride, dry to obtain polyether additive.
[0012] Preferably, in (1), the mass ratio of polyetheramine to glutaraldehyde is 100:(5-6).
[0013] Preferably, the temperature during the reaction in (1) is 55-70℃ and the time is 6-8h.
[0014] Preferably, the temperature for the continued reaction in (1) is 20-30℃ and the time is 4-6h.
[0015] Preferably, in (2), the mass ratio of polyether precursor to maleic acid is 100:(6-15).
[0016] Preferably, the reaction temperature in (2) is 70-80℃ and the reaction time is 12-24h.
[0017] The preferred method for preparing paving stones from high-content lithium carbonate tailings is as follows: terrazzo, aggregate, bentonite, magnesia refractory mud, bauxite, clay, pottery clay, polyether additives, and water are mixed and added to a crusher for crushing and mixing. The mixture is then poured into a mold, pressed into shape, demolded, dried, and placed in a kiln for high-temperature sintering and cooling to obtain paving stones from high-content lithium carbonate tailings.
[0018] Preferably, the high-temperature sintering involves raising the temperature from room temperature to 550-650℃ at a rate of 10-20℃ / min, holding it at that temperature for 1-2 hours, and then raising the temperature to 1050-1200℃ and holding it at that temperature for 2-3 hours.
[0019] (III) Beneficial technical effects: This invention crushes, mixes, blends, and sinters lithium carbonate tailings, coarse sand, terrazzo, bentonite, bauxite, clay, polyether additives, etc., to obtain paving stones with high lithium carbonate tailings content. The lithium carbonate tailings contain a small amount of lithium oxide, which forms a low eutectic glass phase with sodium and potassium oxides in the raw material system. This can play a fluxing effect, improve the sintering performance of the paving bricks, and help improve the mechanical properties of the paving stones.
[0020] The polyether additive of the present invention contains a large number of carboxyl groups, which interact with the surfaces of aggregates, bentonite, clay and other materials, and can act as a dispersant to improve the processing fluidity and dispersibility of the mixture, thereby further enhancing the mechanical strength and modulus of rupture of the paving stone and extending its service life.
[0021] The polyether additive of the present invention contains polyether segments. During the high-temperature sintering process, the polyether segments are easily pyrolyzed and volatilized, leaving pores in the paving stone matrix, thereby improving the apparent porosity and water absorption rate of the paving stone. It has both good water permeability and mechanical strength. When used in outdoor scenarios, rainwater can quickly infiltrate into the ground, which helps to avoid water accumulation on roads during rainy days and reduce the burden on urban drainage systems. Detailed Implementation
[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] The coarse sand has a particle size of 2-5 mm, and the lithium carbonate tailings have a particle size of 5-15 mm.
[0024] The particle size of the fine sand is between 0.6 and 1.2 mm. Example 1
[0025] (1) Add 50g of polyetheramine D2000 and 2.6g of glutaraldehyde to 600mL of ethanol, heat to 60℃, stir and react for 6h, reflux during the reaction, add 2.1g of sodium borohydride, react at 20℃ for 6h to reduce the Schiff base C=N bond, distill under reduced pressure, add the product to dichloromethane, wash with saturated sodium chloride, distill under reduced pressure on the organic phase, dry, and obtain the polyether precursor. The reaction formula is: .
[0026] (2) Add 50g of polyether precursor and 3g of maleic acid to 700mL of 40% (v / v) aqueous ethanol solution, heat to 70℃, and stir to carry out Michael addition reaction for 18h. During the reaction, reflux the solution, add sodium hydroxide to neutralize the pH to 8, dry to remove ethanol and water, wash with saturated sodium chloride, and dry to obtain polyether additive. The reaction formula is: .
[0027] (3) Mix 3 kg of terrazzo, 4.7 kg of aggregate (the aggregate consists of coarse aggregate and fine aggregate sand in a mass ratio of 92:8; the coarse aggregate consists of coarse sand and lithium carbonate tailings in a mass ratio of 75:25), 610 g of bentonite, 350 g of magnesia refractory mud, 520 g of bauxite, 1.1 kg of clay, 1.2 kg of pottery clay, 30 g of polyether additives, and 3.2 kg of water, add them to a crusher for crushing and mixing, then pour them into a mold, press them into shape, demold them and dry them, place them in a kiln and heat them from room temperature to 600°C at a heating rate of 10°C / min, keep them at that temperature for 2 hours, then heat them to 1200°C and keep them at that temperature for sintering for 2 hours, cool them, and you will get paving stones with high lithium carbonate tailings content. Example 2
[0028] (1) Add 50g of polyetheramine D2000 and 3g of glutaraldehyde to 800mL of ethanol, heat to 70℃, stir and react for 6h, reflux during the reaction, add 2.8g of sodium borohydride, react at 30℃ for 4h, distill under reduced pressure, add the product to dichloromethane, wash with saturated sodium chloride, distill under reduced pressure on the organic phase, dry, and obtain the polyether precursor.
[0029] (2) Add 50g of polyether precursor and 5g of maleic acid to 800mL of 60% ethanol aqueous solution, heat to 80℃, stir and react for 12h, reflux during reaction, add sodium hydroxide to neutralize pH to 8, dry to remove ethanol and water, wash with saturated sodium chloride, dry to obtain polyether additive.
[0030] (3) Mix 2.5 kg of terrazzo, 5.7 kg of aggregate (the aggregate consists of coarse aggregate and fine aggregate sand in a mass ratio of 90:10; the coarse aggregate consists of coarse sand and lithium carbonate tailings in a mass ratio of 65:35), 530 g of bentonite, 310 g of magnesia refractory mud, 470 g of bauxite, 0.8 kg of clay, 1.8 kg of pottery clay, 50 g of polyether additives, and 2.8 kg of water, add them to a crusher for crushing and mixing, then pour them into a mold, press them into shape, demold them and dry them, place them in a kiln and heat them from room temperature to 650°C at a heating rate of 10°C / min, keep them at that temperature for 1 h, then heat them to 1050°C and keep them at that temperature for sintering for 3 h, cool them down, and you will get paving stones with high lithium carbonate tailings content. Example 3
[0031] (1) Add 50g of polyetheramine D2000 and 2.5g of glutaraldehyde to 800mL of ethanol, heat to 55℃, stir and react for 8h, reflux during the reaction, add 2.2g of sodium borohydride, react at 20℃ for 6h, distill under reduced pressure, add the product to dichloromethane, wash with saturated sodium chloride, distill under reduced pressure on the organic phase, dry, and obtain the polyether precursor.
[0032] (2) Add 50g of polyether precursor and 7.5g of maleic acid to 0.8L of 60% ethanol aqueous solution, heat to 70℃, stir and react for 24h, reflux during reaction, add sodium hydroxide to neutralize pH to 7, dry to remove ethanol and water, wash with saturated sodium chloride, dry to obtain polyether additive.
[0033] (3) Mix 3.3 kg of terrazzo, 4.2 kg of aggregate (the aggregate consists of coarse aggregate and fine aggregate sand in a mass ratio of 96:4; the coarse aggregate consists of coarse sand and lithium carbonate tailings in a mass ratio of 85:15), 740 g of bentonite, 220 g of magnesia refractory mud, 760 g of bauxite, 0.6 kg of clay, 1.5 kg of pottery clay, 80 g of polyether additives, and 3.2 kg of water, add them to a crusher for crushing and mixing, then pour them into a mold, press them into shape, demold them and dry them, place them in a kiln and heat them from room temperature to 550°C at a heating rate of 20°C / min, keep them at that temperature for 2 hours, then heat them to 1100°C and keep them at that temperature for sintering for 3 hours, and then cool them to obtain paving stones with a high content of lithium carbonate tailings.
[0034] Comparative Example 1 differs from Example 1 in that coarse sand is used instead of lithium carbonate tailings.
[0035] (1) Mix 3kg terrazzo, 4.7kg aggregate (the aggregate consists of coarse aggregate and fine aggregate in a mass ratio of 92:8), 610g bentonite, 350g magnesia refractory mud, 520g bauxite, 1.1kg clay, 1.2kg pottery clay, 30g polyether additive, and 3.2kg water, add them to a crusher for crushing and mixing, then pour them into a mold, press them into shape, demold them and dry them, place them in a kiln and heat them from room temperature to 600℃ at a heating rate of 10℃ / min, keep them at that temperature for 2h, then heat them to 1200℃ and keep them at that temperature for 2h, cool them down and you will get paving stone.
[0036] Comparative Example 2 differs from Example 1 in that no polyether additives are added.
[0037] (1) Mix 3kg terrazzo, 4.7kg aggregate (the aggregate consists of coarse aggregate and fine aggregate sand in a mass ratio of 92:8; the coarse aggregate consists of coarse sand and lithium carbonate tailings in a mass ratio of 75:25), 610g bentonite, 350g magnesia refractory mud, 520g bauxite, 1.1kg clay, 1.2kg pottery clay, and 3.2kg water, add them to a crusher for crushing and mixing, then pour them into a mold, press them into shape, demold them and dry them, place them in a kiln and heat them from room temperature to 600℃ at a heating rate of 10℃ / min, keep them at that temperature for 2h, then heat them to 1200℃ and keep them at that temperature for sintering for 2h, cool them, and you will get paving stones with high lithium carbonate tailings content.
[0038] Comparative Example 3 differs from Example 1 in that a polyether precursor is used instead of a polyether additive.
[0039] (1) Mix 3kg terrazzo, 4.7kg aggregate (aggregate consists of coarse aggregate and fine aggregate sand in a mass ratio of 92:8; coarse aggregate consists of coarse sand and lithium carbonate tailings in a mass ratio of 75:25), 610g bentonite, 350g magnesia refractory mud, 520g bauxite, 1.1kg clay, 1.2kg pottery clay, 30g polyether precursor, and 3.2kg water, add to a crusher for crushing and mixing, then pour into a mold, press into shape, demold and dry, place in a kiln and heat from room temperature to 600℃ at a heating rate of 10℃ / min, hold for 2h, then heat to 1200℃, hold for sintering for 2h, cool to obtain paving stone with high lithium carbonate tailings content.
[0040] Comparative Example 4 differs from Example 1 in that polyacrylic acid (model Jining Tangyi Chemical NP-700) is used instead of polyether additives.
[0041] (1) Mix 3kg terrazzo, 4.7kg aggregate (the aggregate consists of coarse aggregate and fine aggregate sand in a mass ratio of 92:8; the coarse aggregate consists of coarse sand and lithium carbonate tailings in a mass ratio of 75:25), 610g bentonite, 350g magnesia refractory mud, 520g bauxite, 1.1kg clay, 1.2kg pottery clay, 30g polyacrylic acid, and 3.2kg water, add them to a crusher for crushing and mixing, then pour them into a mold, press them into shape, demold them and dry them, place them in a kiln and heat them from room temperature to 600℃ at a heating rate of 10℃ / min, keep them at that temperature for 2h, then heat them to 1200℃ and keep them at that temperature for sintering for 2h, cool them, and you will get paving stones with high lithium carbonate tailings content.
[0042] Example 5 differs from Example 1 in that acrylic acid is used instead of maleic acid.
[0043] (1) Add 50g of polyether precursor and 3g of acrylic acid to 700mL of 40% ethanol aqueous solution, heat to 70℃, stir and carry out Michael addition reaction for 18h, reflux during reaction, add sodium hydroxide to neutralize pH to 8, dry to remove ethanol and water, wash with saturated sodium chloride, dry to obtain polyether additive.
[0044] (2) Mix 3 kg of terrazzo, 4.7 kg of aggregate (the aggregate consists of coarse aggregate and fine aggregate sand in a mass ratio of 92:8; the coarse aggregate consists of coarse sand and lithium carbonate tailings in a mass ratio of 75:25), 610 g of bentonite, 350 g of magnesia refractory mud, 520 g of bauxite, 1.1 kg of clay, 1.2 kg of pottery clay, 30 g of polyether additives, and 3.2 kg of water, add them to a crusher for crushing and mixing, then pour them into a mold, press them into shape, demold them and dry them, place them in a kiln and heat them from room temperature to 600°C at a heating rate of 10°C / min, keep them at that temperature for 2 hours, then heat them to 1200°C and keep them at that temperature for sintering for 2 hours, cool them, and you will get paving stones with a high content of lithium carbonate tailings.
[0045] The water absorption and apparent porosity of the paving stones were tested according to standard GB / T 3810.3-2016. The mechanical properties and modulus of rupture were tested according to standard GB / T 3810.4-2016.
[0046] Table 1 Performance Tests Water absorption rate (%) Apparent porosity (%) Modulus of fracture (MPa) Example 1 5.83 8.74 19.7 Example 2 7.41 11.29 26.3 Example 3 7.69 12.60 21.8 Comparative Example 1 5.67 8.23 18.5 Comparative Example 2 4.15 5.82 17.1 Comparative Example 3 5.60 8.45 17.4 Comparative Example 4 4.47 6.06 18.5 Comparative Example 5 5.70 8.68 18.2 ; The paving stones tested in Examples 1-3 exhibit higher water absorption and modulus of rupture, better permeability, and higher mechanical strength. This is primarily due to the addition of lithium carbonate tailings and polyether additives. The lithium carbonate tailings replace some of the coarse sand as aggregate. The lithium carbonate tailings contain a small amount of lithium oxide, which forms a low-melting-point glass phase with sodium and potassium oxides in the raw material system, acting as a fluxing agent and improving the sintering performance of the paving stones, thus enhancing their mechanical properties. Simultaneously, the added polyether additives contain a large number of carboxyl groups, which interact with the surfaces of aggregates, bentonite, and clay, acting as a dispersant to improve the processing fluidity and dispersibility of the mixture, further enhancing the mechanical strength and modulus of rupture of the paving stones. Furthermore, the polyether additives contain polyether segments, which easily undergo pyrolysis and volatilization during high-temperature sintering, leaving pores in the paving stone matrix, thereby increasing the apparent porosity and water absorption of the paving stones.
[0047] Comparative Example 1 did not include lithium carbonate tailings, resulting in a lower modulus of fracture and poorer mechanical properties in the paving stones.
[0048] Comparative Example 2, which did not contain any polyether additives, had a low modulus of rupture, as well as low apparent porosity and water absorption.
[0049] The polyether precursor added in Comparative Example 3 does not contain carboxyl groups, making it difficult to act as a dispersant. As a result, the paving stone has a low modulus of rupture and poor mechanical properties.
[0050] Comparative Example 4 used conventional polyacrylic acid instead of polyether additives, resulting in paving stones with low apparent porosity and water absorption.
[0051] The acrylic acid and the polyether additives prepared in Comparative Example 5 have low carboxyl content and poor dispersibility, resulting in a low modulus of rupture and poor mechanical properties of the paving stones.
[0052] The above description is merely an illustrative embodiment of the present invention and is not intended to limit the scope of protection of this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A type of paving stone for high-content lithium carbonate tailings, characterized in that, The paving stone of the high-content lithium carbonate tailings comprises 25-33 parts by weight of terrazzo, 42-57 parts by weight of aggregate, 5.3-7.4 parts by weight of bentonite, 2.2-3.5 parts by weight of magnesia refractory mortar, 4.7-7.6 parts by weight of bauxite, 6-11 parts by weight of clay, 12-18 parts by weight of kaolin, and 0.3-0.8 parts by weight of polyether additives. The aggregates include coarse aggregates and fine aggregates in a mass ratio of (90-96):(4-10); the coarse aggregates consist of coarse sand with a particle size of 2-5 mm and lithium carbonate tailings with a particle size of 5-15 mm in a mass ratio of (65-85):(15-35); the fine aggregates consist of fine sand with a particle size of 0.6-1.2 mm. The preparation method of the polyether additive is as follows: (1) Add polyetheramine and glutaraldehyde in a mass ratio of 100:(5-6) to ethanol, stir to react, add sodium borohydride, continue the reaction, distill under reduced pressure, add the product to dichloromethane, wash with saturated sodium chloride, distill under reduced pressure on the organic phase, dry, and obtain polyether precursor. (2) Add polyether precursor and maleic acid in a mass ratio of 100:(6-15) to an ethanol aqueous solution, stir to react, add sodium hydroxide to neutralize, dry to remove ethanol and water, wash with saturated sodium chloride, dry to obtain polyether additive.
2. The paving stone for high-content lithium carbonate tailings according to claim 1, characterized in that, The temperature during the reaction in (1) is 55-70℃ and the time is 6-8h.
3. The paving stone for high-content lithium carbonate tailings according to claim 1, characterized in that, The temperature for the continued reaction in (1) is 20-30℃ and the time is 4-6h.
4. The paving stone for high-content lithium carbonate tailings according to claim 1, characterized in that, The reaction temperature in (2) is 70-80℃ and the reaction time is 12-24h.
5. A method for preparing paving stones from high-content lithium carbonate tailings as described in any one of claims 1-4, characterized in that, The preparation method is as follows: terrazzo, aggregate, bentonite, magnesia refractory mud, bauxite, clay, pottery clay, polyether additives, and water are mixed and added to a crusher for crushing and mixing. Then, the mixture is poured into a mold, pressed and shaped, demolded, dried, placed in a kiln for high-temperature sintering, and cooled to obtain paving stone with high lithium carbonate tailings content.
6. The method for preparing paving stones from high-content lithium carbonate tailings according to claim 5, characterized in that, The high-temperature sintering involves raising the temperature from room temperature to 550-650℃ at a rate of 10-20℃ / min, holding it at that temperature for 1-2 hours, and then raising the temperature to 1050-1200℃ and holding it at that temperature for 2-3 hours.
Citation Information
Patent Citations
Breathable paving bricks and their production methods
CN115784710B
Preparation method of ceramic permeable brick using converter slag and lithium tailings as raw materials
CN109824345A
Color-changeable rock plate and preparation method thereof
CN113896518A
Silicon carbide SDPF with ultrahigh porosity and preparation method thereof
CN116947528A
High-strength refractory castable and preparation method thereof
CN119684017A
